2006
DOI: 10.1586/14737159.6.5.717
|View full text |Cite
|
Sign up to set email alerts
|

Pattern recognition and biomarker validation using quantitative1H-NMR-based metabolomics

Abstract: The collection of global metabolic data and their interpretation (both spectral and biochemical) using modern spectroscopic techniques and appropriate statistical approaches, are known as 'metabolic profiling', 'metabonomics' or 'metabolomics'. This review addresses 1H-nuclear magnetic resonance (NMR)-based metabolomic principles and their application in biomedical science, with special emphasis on their potential in translational research in transplantation, oncology, and drug toxicity or discovery. Various s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
123
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 101 publications
1
123
0
1
Order By: Relevance
“…MS determines the composition of particles based on the mass-to-charge ratio in charged particles. Each technique has distinct advantages and disadvantages (13,27). The major advantages of 1 H-NMR include its unbiased metabolite detection, quantitative nature, and reproducibility (6,7,26).…”
Section: Analytical Platforms For Metabolite Detection and Quantificamentioning
confidence: 99%
See 1 more Smart Citation
“…MS determines the composition of particles based on the mass-to-charge ratio in charged particles. Each technique has distinct advantages and disadvantages (13,27). The major advantages of 1 H-NMR include its unbiased metabolite detection, quantitative nature, and reproducibility (6,7,26).…”
Section: Analytical Platforms For Metabolite Detection and Quantificamentioning
confidence: 99%
“…This is a scientific challenge of the systems biology approach and highlights the need for new knowledge of the relationships and interactions between the components of the system (Figure 2). Monitoring fluctuations of certain metabolites (endogenous low-molecular weight molecules) in body fluids, such as blood (including plasma and serum) and urine, is an important way to detect various human pathologies, including cancer, cardiovascular disease, diabetes, and drug toxicity (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). These data are also needed to construct powerful top-down systems biology tools that link the "omics" disciplines (16).…”
mentioning
confidence: 99%
“…In these applications, statistical pattern recognition techniques were used for data reduction and analysis (23,26,29,41,43), thereby allowing extraction of metabolic information from the complexity of the information-rich data (4,9,14). Although much of this research addressed metabolic variations induced by toxicological exposures (18,24,32), early studies with human plasma demonstrated that 1 H-NMR spectroscopy can also be used to discriminate individuals with cardiovascular disease (4,8,40).…”
mentioning
confidence: 99%
“…This can be done through collection of global metabolic data with modern spectroscopic techniques and appropriate statistical approaches (29,36). Nuclear magnetic resonance (NMR) spectroscopy is one of the major techniques for metabolomics analysis because it allows for simultaneous assessment and quantification of small-molecule metabolites in the concentration range above 10 M. Thus quantitative assessment of various metabolite classes (such as sugars, amino acids, osmolytes, lipids, high-energy phosphates) in tissues and biological fluids can be performed with high-resolution 1 H-and 31 P-NMR spectroscopy.…”
mentioning
confidence: 99%